Independent Agencies and Research Program Performance - Keckler, Charles N. W. (Frontiers in Research Metrics and Analytics, 2022)
Combining performance data from the Bush Administration’s Program Assessment Rating Tool (PART) initiative with measures of organizational independence, I examine whether insulated and plural leadership structures are consequential for the outcomes of the federal programs administered by them. Using regression modelling and controlling for program type, I find that embedding programs in independent agencies is positively and significantly related to ratings of program performance. The effects of independent commissions appear mediated in these models by their positive association with the PART scores given to certain program types, notably research programs. These results are problematic for any global attribution of greater effectiveness to executive agencies under single-headed control and closer presidential direction.